Construction of a superhydrophobic coating using triethoxyvinylsilane-modified silica nanoparticles. (4th May 2019) - Wang, Zhansheng; Yang, Weizhong; Sun, Feng; Zhang, Ping; He, Yi; Wang, Xuekai; Luo, Daibing; Ma, Wangjing; Sergio, Gonzalez-Cortes
ABSTRACT: A novel superhydrophobic film simulating the structure of a lotus leaf was prepared using triethoxyvinylsilane-modified silica (SiO2 ) nanoparticles. The surface characteristics of this coating were studied by scanning electron microscopy, Fourier transform infrared spectroscopy, energy-dispersive spectrometry, atomic force microscope, and static contact angle (CA) measurements. Triethoxyvinylsilane reacted with the hydroxyl groups on the SiO2 surface forming vinyl hydrophobic terminations by ammonia-assisted catalysis. The resulting coating surface showed excellent superhydrophobicity since a CA of 156° could be achieved when the modified silica nanoparticles were coated on glass. This surface repelled aqueous liquids because of its hierarchical roughness and surface vinyl terminations. Its superhydrophobicity and self-cleaning properties were illustrated by the rolling movements of rhodamine-labelled water droplets with red colour on this coating.